THE RESEARCH ON ROTATIONAL SURFACES IN PSEUDO EUCLIDEAN 4-SPACE WITH INDEX 2 - Almaz, F.; Kulahci, M. A. (Comenius Univ, 2023)
. In this study, we define a brief description of the hyperbolic and elliptic rotational surfaces using a curve and matrices in 4-dimensional semi-Euclidean space with index 2. That is, we provide different types of rotational matrices which are the subgroups of M by rotating a selected axis in E24. Also, we choose two parameter matrices groups of rotations and we give the matrices of rotation corresponding to the appropriate subgroup in 4-dimensional semi-Euclidean space. Therefore, we generate surfaces of rotation using Killing vector fields in E24, we restrict to rotational surfaces constructed from starting with a planar curve and we obtain the Gaussian curvature and the mean curvature of these surfaces of rotation.
Keywords: Pseudo Euclidean 4-space; surfaces of rotation; Killing vector field